HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN MINUM ARV (ANTIRETROVIRAL) PADA IBU BALITA ODHIV DI WILAYAH KERJA PUSKESMAS KENCONG JEMBER - Skripsiwati, Lulus Eka; Kiswati, Kiswati; Bachri, Syaiful; Sugijati, Sugijati (HEALTHY : Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
The problems faced by PLHIV are very complex, especially mothers of toddlers with HIV, namely fear of being abandoned by their husbands, being shunned by their families and not believing they are infected with HIV, which affects adherence to taking medication. ARV (AntiRetroviral) therapy is a lifelong therapy, requiring high compliance of at least 95% of the dose, so family system support is needed in ARV drinking management. OnART data from Kencong Health Center shows 234 PLHIV and LFU data shows 35 PLHIV. The purpose of this study was to determine the relationship between family support and adherence to taking ARV (AntiRetroviral) in mothers of toddlers with HIV in the Kencong Health Center Jember work area. The research design was observational analytic with a case control study approach with a questionnaire as a measuring instrument. The population of this study was 54 mothers of toddlers with a sampling technique of total sampling. The results of the calculation showed that almost all mothers of toddlers with HIV received support of 94.44% and almost all mothers of toddlers with HIV were compliant in taking ARVs of 79.63%. The results of the Chi Square test obtained a p value of 0.040 <0.05, meaning that there is a relationship between family support and adherence to taking ARV (AntiRetroviral) in mothers of toddlers with HIV in the Kencong Jember Health Center work area with a fairly close relationship. It is hoped that health workers will provide information and education about ARV treatment by involving families in order to increase family support for adherence to taking ARV drugs. ABSTRAKMasalah yang dihadapi ODHIV sangatlah komplek khususnya ibu balita ODHIV yaitu takut ditinggalkan suami, dijauhi keluarga dan tidak percaya terinfeksi HIV sehingga mempengaruhi kepatuhan minum obat. Terapi ARV (AntiRetroviral) adalah terapi seumur hidup, memerlukan kepatuhan tinggi minimal 95% dari dosis maka dibutuhkan support sistem keluarga dalam manajemen minum ARV. Data OnART Puskesmas Kencong ada 234 ODHIV dan data LFU ada 35 ODHIV. Tujuan Penelitian yakni mengetahui hubungan dukungan keluarga dengan kepatuhan minum ARV (AntiRetroviral) pada ibu balita ODHIV di wilayah kerja Puskesmas Kencong Jember. Desain penelitian adalah analitik obsevasional dengan pendekatan case control study dengan alat ukur kuesioner. Populasi penelitian ini sebanyak 54 ibu balita ODHIV dengan teknik pengambilan sample yaitu total sampling. Hasil dari perhitungan hampir seluruh ibu balita ODHIV mendapatkan dukungan sebanyak 94,44% dan hampir seluruh ibu balita ODHIV patuh minum ARV sebanyak 79,63%. Hasil uji Chi Square didapatkan p value 0,040< 0,05 artinya ada hubungan dukungan keluarga dengan kepatuhan minum ARV (AntiRetroviral) pada ibu balita ODHIV di wilayah kerja Puskesmas Kencong Jember dengan keeratan hubungan cukup. Diharapkan petugas kesehatan memberikan informasi dan edukasi tentang pengobatan ARV dengan melibatkan keluarga guna meningkatkan dukungan keluarga terhadap kepatuhan minum obat ARV.